Google Classroom as E-learning Mode at SMP YPM 7 Sidoarjo - Rangga Kusuma Admaja; J. Priyanto Widodo; Fabiola D. Kurnia (STKIP PGRI SIDOARJO, 2020)
Technology has grown speedily so that people can access the internet and also can communicate with others easily. By means the development of technology, many people use it not only as a communication tool but also for the implementation in the educational world in regard students learn to use computers and all things about technology. Furthermore, students and teacher can also do teaching and learning activities online, Google Classroom, as one of the online learning platforms that applied at SMP YPM 7 Sidoarjo. Based on the background of the study, the purpose of the study focuses to discribe How is the implementation of e-learning by using google classroom at SMP YPM 7 Sidoarjo and what the students’ perception. In order to answer the two formulated research questions, there are two types of instruments in this research. Those obtained from document google classroom and questionnaire. This is a qualitative research design the writer describe the data briefly. This research conducted under the assumptions there are various perceptions towards the implementation of google classroom as E-learning at SMP YPM 7 Sidoarjo. Whereas, the result of the questionnaire explain about the Perception of the student, the instrument showed that the student’s majority had a positive Perspection. The conclusion in this research is there is neccesity to elaborate some suggestions regarding google classroom as e-learning the The teacher should be more explore application of google classroom it self.